(untitled) (Sinología hispánica. China Studies Review, 2017)
This study focuses on one of the important and difficult language points in teaching Chinese as the second language, synonymous degree adverbs in modern Chinese language, aiming at the beginning level of occidental students who excessively rely on their mother tongue. The research has been done by observing a group of typical adverbs with the meaning of “very” in Chinese language, such as "feichang, shifen, hen, ting, ji" in combination with ontology and error analysis and classroom testing. The paper explores the reasons and types of errors, and designs the teaching plan according to the testing results. Comparing the testing results, it is suggested that compare with error analysis, language testing combined with inductive reasoning is more effective in teaching synonymous degree adverbs in modern Chinese language.